The Heritage on Our Plates: Reviving Traditional Diets for Modern Wellbeing (Advances in Applied Biological Research, 2025)
Traditional dietary patterns, developed over centuries, offer balanced nutrient  profiles, cultural sustainability, and health benefits that are increasingly relevant  in addressing modern diet-related chronic diseases. With rising rates of non communicable diseases (NCDs) such as cardiovascular disease, type 2 diabetes and  obesity, global interest in diets like the Mediterranean, Indian traditional, Japanese  and Nordic patterns has surged. These diets are rich in whole grains, fresh vegetables,  fruits, legumes, nuts, healthy fats and fermented foods and low in processed sugars  and trans fats. This review synthesizes recent literature (2018–2025) on the nutrient  composition, health outcomes and potential integration strategies of traditional diets  in contemporary health systems. Also explore the challenges of preserving cultural  dietary practices in an era dominated by fast food and ultra-processed products.  Data indicate that adopting traditional diets can reduce cardiovascular risk by up  to 30%, improve glycaemic control, and support gut microbiota diversity, leading  to improved overall well-being. The review concludes with recommendations for  policymakers, healthcare providers, and individuals to adapt and sustain these  dietary patterns in the modern context.
Keywords: Traditionaldiets; Mediterranean diet; Indian diet; Japanese diet; Nordic diet; chronic diseases; nutrition and health